ON THE EVOLUTION OF RADIO EMISSION OF THE TYCHO BRAHE’S SUPERNOVA REMNANT (3C10) - Vinyajkin, E. N. (Одеські астрономічні публікації, 2017)
Basing on long-term (1966-1998) measurements at the frequency 86 MHz the mean rate of the secular decrease of Tycho Brahe’s supernova remnant (SNR) radio emission flux density has been estimated as (0.92 ± 0.70)%yr -1. The decrease of Tycho Brahe’s SNR radio emission is not uniform in time. The rate of the secular decrease of this SNR radio emission is frequency independent in the limits of the errors. The weighted mean value of the rate of the secular decrease of the Tycho Brahe’s SNR radio emission in the frequency range 86-5000 MHz is (0.41 ± 0.02)%yr -1.